Occupational Safety Knowledge Management with Performance Indicators as a Strategy for the Reduction of Accidents in the Construction Sector in Mexico - Quintero, Martha Patricia; Pérez, Juan Carlos; López, Gerardo de Jesús; Olivera, Emmanuel (European Scientific Journal, ESJ, 2017)
The construction industry is one of the key contributors to a country’s economy. It accounts for 13.4% of total annual production. The construction sector has specific characteristics such as dynamic work and uncertain conditions; therefore, it tends to cause occupational accidents. Another one of its features is the temporary nature of its projects. This characteristic leads to the loss of learning and disappearance of workers at the end of each project inhibiting workers from gaining experience. The aim of this paper is to propose a model of knowledge management in occupational safety that limits or stops the loss of knowledge, covers the dynamic needs of the construction sector and helps to reduce accidents at work. The present research method is exploratory; it identifies the elements or strategies of the stages of knowledge management that allow the reduction of accidents in the construction sector. As a result of this research, the authors have proposed a model which is able to manage the knowledge generating learning from its elements. Some key safety performance indicators as strategies to reduce occupational accidents are discussed.